Schwannomatosis of the Spinal Accessory Nerve: A Case Report - Morshed, Ramin A.; Lee, Anthony T.; Lee, Young M.; Chin, Cynthia T.; Jacques, Line (Journal of Brachial Plexus and Peripheral Nerve Injury, 2019)
Schwannomatosis is a distinct syndrome characterized by multiple peripheral nerve schwannomas that can be sporadic or familial in nature. Cases affecting the lower cranial nerves are infrequent. Here, the authors present a rare case of schwannomatosis affecting the left spinal accessory nerve. Upon genetic screening, an in-frame insertion at codon p.R177 of the Sox 10 gene was observed. There were no identifiable alterations in NF1, NF2, LZTR1, and SMARCB1. This case demonstrates a rare clinical presentation of schwannomatosis in addition to a genetic aberration that has not been previously reported in this disease context.
Keywords: spinal accessory nerve tumor; schwannomatosis; schwannoma; neck mass; diffusion tensor imaging